2020
DOI: 10.3758/s13421-019-01009-0
|View full text |Cite
|
Sign up to set email alerts
|

The phenomenology of remembering our moral transgressions

Abstract: People tend to believe that they truly are morally good, and yet they commit moral transgressions with surprising frequency in their everyday lives. To explain this phenomenon, some theorists have suggested that people remember their moral transgressions with fewer details, lower vivacity, and less clarity, relative to their morally good deeds and other kinds of past events. These phenomenological differences are thought to help alleviate psychological discomfort and to help people maintain a morally good self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Also, the more severe the moral transgression, the better we recall it, especially when we perpetrated it [7]. This seems to occur even though recalling severe, self-perpetrated moral violations are accompanied by more intense negative affect and psychological distress than recalling more minor ones [7,8]. To the best of our knowledge, there are no studies that examine the effects of recalling memories of moral transgressions during which people perceived themselves as both victims and perpetrators [2], such as PMIEs.…”
Section: Autobiographical Episodic Memories Of Moral Transgressionsmentioning
confidence: 99%
“…Also, the more severe the moral transgression, the better we recall it, especially when we perpetrated it [7]. This seems to occur even though recalling severe, self-perpetrated moral violations are accompanied by more intense negative affect and psychological distress than recalling more minor ones [7,8]. To the best of our knowledge, there are no studies that examine the effects of recalling memories of moral transgressions during which people perceived themselves as both victims and perpetrators [2], such as PMIEs.…”
Section: Autobiographical Episodic Memories Of Moral Transgressionsmentioning
confidence: 99%
“…Several recent studies have shown that, when prompted to do so, people can readily recall having committed many different moral transgressions from their recent and distant pasts-some of which they even judge to be extremely morally wrong (Escobedo & Adolphs, 2010;Hofmann, Wisneski, Brandt, & Skitka, 2014;Stanley, Henne, Iyengar, Sinnott-Armstrong, & De Brigard, 2017. The process of retrieving these moral transgressions is commonly accompanied by intense negative affect and distress (Escobedo & Adolphs, 2010;Huang et al, 2020;Stanley et al, 2017). Critically, Huang et al (2020) found not only that people can readily recall their own moral transgressions they judge to be extremely morally wrong, but also that more severe moral transgressions are reportedly recalled more frequently (both voluntarily and involuntarily), with more detail, and with a stronger sense of reliving.…”
Section: Two Perspectives On Memory For Moral Transgressionsmentioning
confidence: 99%
“…In contrast, other research suggests that people can and do readily recall many of their own past moral transgressions instead of forgetting them (Huang, Stanley, & De Brigard, 2020; Stanley & De Brigard, 2019; Stanley, Bedrov, Cabeza, & De Brigard, 2020). Several recent studies have shown that, when prompted to do so, people can readily recall having committed many different moral transgressions from their recent and distant pasts—some of which they even judge to be extremely morally wrong (Escobedo & Adolphs, 2010; Hofmann, Wisneski, Brandt, & Skitka, 2014; Stanley, Henne, Iyengar, Sinnott‐Armstrong, & De Brigard, 2017, 2019, 2020).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations